Management High Grade Glioma in Elderly - Sofyan, Henry Riyanto; Pratiwi, Intan; Fahmi Radityamurti; Anastasia Asylia Dinakrisma; Aninditha, Tiara; Savitri, Irma (Acta Neurologica Indonesia, 2025)
Introduction: High-grade glioma (HGG) is an aggressive primary brain tumor with poor prognosis, particularly in elderly patients. Management is complex due to comorbidities, decreased functional status, and increased risk of treatment-related toxicity. Personalized approaches balancing efficacy and quality of life are essential in this population. Case Report: A 67-year-old male presented with progressive headache, limb weakness, and visual disturbances. MRI revealed a large right temporoparietal lesion suggestive of HGG. Craniotomy and biopsy confirmed a high-grade glioma. The patient had a Karnofsky Performance Status (KPS) of 40, with significant cognitive and functional impairments, along with comorbidities including diabetes and hypertension. Given his frailty, he was treated with hypofractionated radiotherapy and concurrent temozolomide. Discussion: Treatment decisions in elderly HGG patients should consider age, KPS, cognitive status, and comorbidities. Hypofractionated radiotherapy combined with temozolomide is effective and better tolerated in frail patients. Multidisciplinary care is crucial to manage physical, cognitive, and emotional needs. Cognitive assessment before therapy aids in anticipating treatment impact. Prophylactic treatment for opportunistic infections such as Pneumocystis jirovecii is recommended during chemotherapy. Conclusion: Elderly patients with HGG require individualized, multidisciplinary care. Factors such as performance status, cognitive function, and comorbidities must guide treatment to achieve optimal outcomes while preserving quality of life